Lost boy : this is my story - Jeffs, Brent W.; Szalavitz, Maia. (New York : Broadway Books, 2009)
Former Fundamentalist Church of Jesus Christ of Latter-day Saints member Brent Jeffs reveals both the terror and the love he experienced growing up on his prophet's compound-- and the harsh exile existence that so many boys face once they have been expelled by the sect.
Includes bibliographical references.
Keywords: Jeffs, Brent W; Fundamentalist Church of Jesus Christ of Latter Day Saints; Polygamy -- United States; Mormons -- United States -- Biography; Sex crimes -- United States; Mormon fundamentalism -- United States